Uranium in Nepal: A power struggle on its utilization (Rajarshi Janak University Research Journal, 2025)
Uranium is a key component for sustainable nuclear energy and effective resource management. This study investigates the complex dynamics surrounding natural uranium resources in Upper Mustang, Nepal, focusing on local, national, and international interests and the power struggles that emerge from competing stakeholders’ objectives. Using a qualitative approach, 32 in-depth interviews were analyzed through thematic and narrative interpretation. Findings show a strong local desire for resource preservation. However, concerns over the technical and financial requirements of uranium management suggest potential reliance on national or international support. The unanimous endorsement of the Nepal Army for site security reflects a high level of trust in the military to protect this strategically significant resource. The study reveals a strong local opposition to foreign involvement. Although there is significant interest in resource extraction for economic benefit, with 23 participants open to selling under certain conditions, participants emphasize the need for equitable benefit-sharing and responsible governance. Applying Elite Theory, Social Conflict Theory, Community Based Natural Resource Management System, and Dependency Theory, the study highlights the intricate balance required to manage Upper Mustang's uranium while addressing local needs, national interests, and geopolitical sensitivities.